Community Preparedness in Facing Flood Disasters in Kecamatan Baolan, Kabupaten Tolitoli - Alfrida Semuel Ra'bung; T. Iskandar Faisal; I Kadek Wartana (Poltekkes Kemenkes Palu, 2026)
Background: Kelurahan Baru RT 01 RW 12 Kecamatan Baolan is one of the areas that often experiences floods and has an impact on property destruction, clean water difficulties and poses a risk of disease, so community preparedness is needed to minimize the impact caused. This study aims to analyze community preparedness in dealing with flood disasters in Baolan District, Tolitoli Regency . Methods: This study uses a survey method with a correlational approach which was carried out in Baru Village, RT 01 RW 12, Baolan District from June 11 to 13, 2024. The research sample consisted of all heads of families residing in the area, totaling 102 heads of families. The research variable is community preparedness in dealing with flood disasters. The instrument used was in the form of a preparedness questionnaire that included five parameters, namely: knowledge, attitude, emergency response plan, early warning system, and resource mobilization. Data analysis uses the Pearson product moment test, as well as multiple linear regression tests with a 95% confidence interval (CI). Results: The results of the study showed that community preparedness was in the category of very ready (69.6%). There was a significant relationship between knowledge parameters (p=0.000; r=0.822), attitudes (p=0.000; r=0.609), emergency response plans (p=0.000; r=0.862), early warning systems (p=0.000; r=0.642), and resource mobilization (p=0.000; r=0,623) and disaster preparedness (p<0.05). Of the five parameters, knowledge is the most influential factor on preparedness (p=0.000; beta=0.435). Conclusion: The community in the research area is classified as very prepared to face flood disasters, with knowledge as the most influential factor. These findings suggest that increased public knowledge about flood disaster risk plays a key role in improving preparedness. This emphasizes the importance of continuous education programs to strengthen public knowledge and awareness.